Proteinograma sérico, nível glicêmico e mensuração de peso em potros neonatos da raça mangalarga marchador - Bromerschenkel, Ingrid (2014)
In equine clinic often faced with the difficulty of interpreting results of biochemical tests due to scant references for comparison. Glucose is the main substrate used by the body to perform different biological functions. Blood glucose is in constant flux, being transported to various parts of the body and within each animal species variations of glycemia primarily a function of age, diet and physical conditions occur. The literature cites a number of mathematical models to estimate horses weight, based on body measurements and adapted tapes generated by these models. However, these models or weight tapes are not always suitable for all breeds and ages, and some techniques for estimating body weight reproduce more accurate results than others depending on these factors. Thus, this study aimed to establish the protein serum concentrations in healthy foals Mangalarga Marchador the neonatal period; evaluate the use of portable glucometer for blood glucose measurements, considering how control the results measured by laboratory test and determine if the variation of glycemia measured by portable glucose is in agreement with the Food and Drug Administration; determine plasma glucose concentrations during the neonatal period using laboratory testing and; compare four methods for measuring weight and verify the accuracy of each in relation to the actual weight of the animal measured in trade balance. There was no significant variation of protein fractions between the times. The foals were no significant changes in glucose concentrations during the neonatal period. The portable glucose showed similar accuracy for laboratory test to determine glucose levels in neonatal foals. The average rate of glucometer error remained within the limits required by the Food and Drug Administration. And in foals 12 hours to 30 days old can adopt the F2 and FMAPE as an alternative method for measuring weight, since the results of any of these methodologies differ measured by the scales.